A pilot non‐inferiority randomized controlled trial to assess automatic adjustments of insulin doses in adolescents with type 1 diabetes on multiple daily injections therapy - El Fathi, Anas; Palisaitis, Emilie; Oettingen, Julia E.; Krishnamoorthy, Preetha; Kearney, Robert E.; Legault, Laurent; Haidar, Ahmad (Pediatric diabetes, 2020)
Background Multiple daily injections (MDI) therapy for type 1 diabetes involves basal and bolus insulin doses. Non‐optimal insulin doses contribute to the lack of satisfactory glycemic control. We aimed to evaluate the feasibility of an algorithm that optimizes daily basal and bolus doses using glucose monitoring systems for MDI therapy users. Methods We performed a pilot, non‐inferiority, randomized, parallel study at a diabetes camp comparing basal‐bolus insulin dose adjustments made by camp physicians (PA) and a learning algorithm (LA), in children and adolescents on MDI therapy. Participants wore a glucose sensor and underwent 11 days of daily dose adjustments in either arm. Algorithm adjustments were reviewed and approved by a physician. The last 7 days were examined for outcomes. Results Twenty‐one youths (age 13.3 [SD, 3.7] years; 13 females; HbA1c 8.6% [SD, 1.8]) were randomized to either group (LA [n = 10] or PA [n = 11]). The algorithm made 293 adjustments with a 92% acceptance rate from the camp physicians. In the last 7 days, the time in target glucose (3.9‐10 mmol/L) in LA (39.5%, SD, 20.7) was similar to PA (38.4%, SD, 15.6) (P = .89). The number of hypoglycemic events per day in LA (0.3, IQR, [0.1‐0.6]) was similar to PA (0.2, IQR, [0.0‐0.4]) (P = .42). There was no incidence of severe hypoglycemia nor ketoacidosis. Conclusions In this pilot study, glycemic outcomes in the LA group were similar to the PA group. This algorithm has the potential to facilitate MDI therapy, and longer and larger studies are warranted.